Fundusze inwestycyjne w procesach sekurytyzacji wierzytelności w Polsce - Buszko, Michał (Investments Funds in the Process of Receivables Securitization in Poland, 2006)
Securitization is one of the most dynamically developing financial technique the European Union capital markets. In Poland such a kind of transaction is not widely spread. In practice there were conducted just few securitization processes, mostly related to receivables created by medical services entities. When analyzing the main barriers of securitization in Poland, one has to lake into consideration the lack of concise law regulations, the complicated nature of securitization itself and high costs of receivables trade agency. To omit the largest obstacles in developing the securitization in Poland, in the year 2004 Polish Parliament voted the new investment funds act and an amendment of the Polish banking law. These two acts implement new solutions enhancing securitization of banking assets and enable establishing the securitization funds participating in securitization processes as SPV. This paper presents essential aspects of functioning of such funds and focuses on main advantages as well as problems of their financing and investing activities.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 94-102